The determinants of housing price in Sabah, Malaysia / Muhammad Atiq Aiman Mohd Sedek - Mohd Sedek, Muhammad Atiq Aiman (2019)
Residential homes are a basic necessity for the community to improve their quality of life as well as economic goods to the nation. This study points to look at the determinants of Housing Price in Sabah from 2000 until 2017. The nonstop increase of housing price in Sabah is becoming one of the hot issues talked about these days. This study applied four basic theories which concern with four major issues which are the population growth, the location and physical attributes, demand and supply and the last one is externalities. Basically, the theories used in this study deal with these four factors which influence the rate of house pricing. Ordinary Least Square (OLS) method is implemented to this study. The findings give benefit to various parties such as investors, housing developers, speculators and home buyers. The results concluded that size floor and population growth have the major effects in determining the housing price.